Modern Beekeeping Bases for Sustainable Production - Eduardo Rebolledo Ranz, Ramón (IntechOpen, 2020)
Beekeeping worldwide has seen remarkable development in the face of the growing demand for products from bees by consumers who demand increasingly innocuous products that do not harm the environment. However, it should be noted that, recently, problems have arisen in beekeeping production that could become restrictive factors for the worldwide development of beekeeping. This book includes, in simple and accessible terms, very relevant topics such as the effect of pesticides, the impact of diseases and their management, production and analysis of pollen present in honey, DNA analysis, and sustainable management, among others. This book is answering an expected need for accurate and international information for the productive sector.